Effects of Social Media on Adolescents' Willingness and Intention to Use E-Cigarettes: An Experimental Investigation. Issue 4 (8th January 2020) - Vogel, Erin A; Ramo, Danielle E; Rubinstein, Mark L; Delucchi, Kevin L; Darrow, Sabrina M; Costello, Caitlin; Prochaska, Judith J
Abstract: Introduction: This study examined the effects of experimentally manipulated social media exposure on adolescents' willingness and intention to use e-cigarettes. Aims and Methods: Participants were 135 adolescents of age 13–18 (52.6% female, mean age = 15.3) in California. Participants viewed six social media posts online in a 2 (post source: peer or advertisement) × 2 (e-cigarette content exposure: heavy or light) between-subjects design. Analyses were weighted to population benchmarks. We examined adolescents' beliefs, willingness, and intention to use e-cigarettes in association with social media use intensity in daily life and with experimentally manipulated exposure to social media posts that varied by source (peer or advertisement) and content (e-cigarette heavy or light). Results: Greater social media use in daily life was associated with greater willingness and intention to use e-cigarettes and more positive attitudes, greater perceived norms, and lower perceived danger of e-cigarette use (all p -values <.01). In tests of the experimental exposures, heavy (vs. light) e-cigarette content resulted in greater intention ( p  = .049) to use e-cigarettes and more positive attitudes ( p  = .019). Viewing advertisements (vs. peer-generated posts) resulted in greater willingness and intention ( p -values <.01) to use e-cigarettes, more positive attitudes ( p  = .003), and greater norm perceptions ( p  = .009). The interaction effect of post source by post content was not significant for any of the outcomes (all p -values >.529). Conclusions: Greater social media use and heavier exposure to advertisements and e-cigarette content in social media posts are associated with a greater risk for e-cigarette use among adolescents. Regulatory action is needed to prohibit sponsored e-cigarette content on social media platforms used by youth. Implications: Adolescents who use social media intensely may be at higher risk for e-cigarette use. Even brief exposure to e-cigarette content on social media was associated with greater intention to use and more positive attitudes toward e-cigarettes. Regulatory action should be taken to prohibit sponsored e-cigarette content on social media used by young people, including posts by influencers who appeal to young people.